Deforestación de la costa peruana: rasgos de un proceso secular - Seiner-Lizárraga, Lizardo (2023)
This study seeks to identify the main factors that have most directly influenced the coastal deforestation process on a secular scale are identified. There are five factors that can be identified as generators of coastal forest deterioration: domestic use for construction and use of firewood for cooking food; use of wood in mining and metallurgical activities and employment in shipbuilding as well as in land transport with the arrival and spread of railways.